Mastering Ansible : master the ins and outs of advanced operations with Ansible - Keating, Jesse (Packt Publishing, 2017)
Master the ins and outs of advanced operations with Ansible About This Book Learn how to extend Ansible with custom modules, plugins, and inventory sources Utilize advanced Ansible features to orchestrate rolling updates with little to no service disruptions An up-to-date book that brings to light the newly added features in Ansible 2.x Who This Book Is For This book is for Ansible developers and operators who have an understanding of the core elements and applications but are now looking to enhance their skills in applying automation using Ansible. What You Will Learn Gain an in-depth understanding of how Ansible works under the covers Fully automate the Ansible playbook executions with encrypted data Access and manipulate variable data within playbooks Use Blocks to construct failure recovery or cleanup Explore the Playbook debugger and Ansible Console Troubleshoot unexpected behavior effectively Work with cloud infrastructure providers and container systems Develop custom modules, plugins, and dynamic inventory sources In Detail This book provides you with the knowledge you need to understand how Ansible 2.1 works at a fundamental level and leverage its advanced capabilities. You'll learn how to encrypt Ansible content at rest and decrypt data at runtime. You will master the advanced features and capabilities required to tackle the complex automation challenges of today and beyond. You will gain detailed knowledge of Ansible workflows, explore use cases for advanced features, craft well thought out orchestrations, troubleshoot unexpected behaviour, and extend Ansible through customizations. Finally, you will discover the methods used to examine and debug Ansible operations, helping you to understand and resolve issues. By the end of the book, the readers will be able to unlock the true power of the Ansible automation engine and will tackle complex real world actions with ease. Style and approach This clear, practical guide illustrates the advanced functionalities of Ansible, its system architecture, and design aspects that will help you to master Ansible with ease. Downloading the example code for this book. You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the code file.